The project management handbook a guide to capital improvements - Vida, Kevin P. (Government Institutes, 2012)
This book provides a clear explanation of the roles and responsibilities a project manager must fulfill in executing a Capital Improvement Program (CIP) project successfully. It begins with the basics of project management and traces the life cycle of the CIP project from start to finish. It is an essential resource for students and professionals.